2018
DOI: 10.1029/2018gl078293
|View full text |Cite
|
Sign up to set email alerts
|

Giant Pulsations Excited by a Steep Earthward Gradient of Proton Phase Space Density: Arase Observation

Abstract: We present observational evidence of drift resonance between westward propagating odd mode standing ultralow frequency waves and energetic protons. Compressional ∼13 mHz (Pc4 band) waves and proton flux oscillations at >50 keV were detected at ∼03 hr magnetic local time by the Arase satellite on 15 April 2017. The azimuthal wave number (m number) is estimated to be ∼−50 from ground observations, while the theory of drift resonance gives m ∼− 49 for odd mode waves and ∼110‐keV protons, providing evidence that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…Southwood et al (1969) has proposed that poloidal mode waves are associated with the drift‐bounce resonance in a homogeneous field. Recently, Yamamoto et al (2018) observed the excitation of compressional pulsations propagating westward with the m number of m = − 50 around the magnetic equator. The waves were odd mode waves and in the drift resonance with energetic ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Southwood et al (1969) has proposed that poloidal mode waves are associated with the drift‐bounce resonance in a homogeneous field. Recently, Yamamoto et al (2018) observed the excitation of compressional pulsations propagating westward with the m number of m = − 50 around the magnetic equator. The waves were odd mode waves and in the drift resonance with energetic ions.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to see that these wave properties are actually seen in the simulation as shown in Figure 3. Yamamoto et al (2018) consider that the Pc5 waves are mainly compressional because dB r of fundamental mode is small, and compressional mode becomes prominent around the magnetic equator (Takahashi et al, 1992). Since we show the global distribution of Pc5 waves at MLAT = 1° in Figure 3, this interpretation can qualitatively explain the excited Pc5 polarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that this transverse Pc3-4 wave is not due to upstream waves. Instead, a possible explanation is the fundamental standing wave caused by the drift-bounce resonance (e.g., Dai et al 2013;Oimatsu et al 2018;Yamamoto et al 2018), although we do not further discuss this possibility, because it is beyond the scope of this study.…”
Section: Signatures Of Standing Alfvén Waves and Upper Hybrid Resonanmentioning
confidence: 99%
“…Pc4-5 toroidal waves with low m are usually considered to be caused by external sources, such as Kelvin-Helmholtz instability along the magnetopause (e.g., Claudepierre et al, 2008;Ling et al, 2018;Rae et al, 2005;Zhang et al, 2018), solar wind dynamic pressure impulse (e.g., Allan et al, 1986;Degeling et al, 2014;Lee & Lysak, 1989;Shen et al, 2015Shen et al, , 2017Shi et al, 2013Shi et al, , 2014Tian et al, 2016;Zong et al, 2012), and foreshock transients (e.g., Hartinger et al, 2013;Shen et al, 2018). Pc4-5 poloidal waves with high wave number are usually driven by localized kinetic plasma instabilities such as the drift-bounce resonance instability (e.g., Oimatsu et al, 2018;Southwood, 1976;Yang et al, 2010), the free energy could be generally provided by bump-on-tail distribution at low-energy (~1-10 keV; e.g., Liu et al, 2013;Shi et al, 2018;Takahashi et al, 2018) or inward gradient of ion phase space density (PSD) at high energy (tens to hundreds of keV; e.g., Dai et al, 2013;Min et al, 2017;Yamamoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%